Plant density and pruning effects on leaf production of Morus Alba cultivars - Rúbia, Antonio Castilho; Rocha, Tulio Ribeiro da; Abreu, Clovis Pompilio de (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1976)
Leaf production in three consecutives years of the Calabreza, Fernão Dias and Lopes Lins cultivars of Morus alba was analysed. They were planted at the densities of 6670, 4440 and 3330 plants per hectarand were submitted to three pruning operations during the year. At each pruning the stems were out very low almost at the soil surface. Calabreza cultivar gavethe highest leaf yields at the density of 6670 plants per hectar and July revealed to be the highest yielding pruning season. The Lopes Lins cultivar gave the lowest yields.